Imagética germânica na construção do olhar fotográfico: nos tempos do Estado Novo - Silva, Miguel Furtado Freire da (2011)
The framework of this research is assembled under the assumption that there is a photo-cinematographic look distinguished by Third Reich Germany, we nominate it Germanic look. The transit of this imagetic has reached some communication parts which have built Brazilian estadonovista ideology portrait. Not only fixed photograph, which has gained room in graphic publications, specially in the neverbefore- released magazine Obra Getuliana, but also the cinematographic image recorded in short films produced by Cine Jornal Brasileiro do Departamento de Imprensa e Propaganda DIP reveal different plasticity construction that denotes reflex of the influence, as well as a will to get closer to the Germanic treatment given to the advertising diffusion pieces of Adolf Hitler thoughts. In Estado Novo, the images have received a new meaning. They were ascribed as having primacy in representing a new era, shaping a recreated nation, home and motherland of a new man. Considered similar to the written word, photography has divided graphic space into journalistic periodicals and advertising pamphlets. Inside the cinematographic journals it has reined as the carrier of the true facts, always followed by the verbal texts that cinema had appropriated from the accredited radio programs. The new means of communication fitted perfectly into the idea of renovation, apparent innovation, many times being mistaken for modernization. Therefore, modernization decanted by the governmental regime is symbolically established through recent media. This is the nuclear issue of the thesis, in order to reach it we undergo an intra-frame analysis, specially, the constituting elements of the photography new esthetics, which are re-presented as if they were breaking through the traditional canons of photographs, determining a new plastic composition of photocinematographic imagetic.